Vocational Innovation in Blockchain-Based Traceability: Enhancing Authenticity, Sustainability, and Consumer Engagement in Gayo Coffee Supply Chains - Indra Akbar; A Azlina; Desy Puspita; Iswandi Idris (Journal of Science and Education (JSE), 2025)
This study presents the design and implementation of a blockchain and QR-based traceability system aimed at enhancing authenticity, sustainability, and consumer engagement within the Gayo coffee supply chain in Aceh, Indonesia. A design-based research (DBR) approach was adopted through three iterative stages: (i) problem analysis and stakeholder mapping with cooperatives, exporters, and auditors, (ii) prototype development of a permissioned blockchain integrated with smart contracts and QR interfaces, and (iii) field validation with twenty Gayo coffee MSMEs across Bener Meriah and Aceh Tengah. System performance was evaluated using black-box functional testing, System Usability Scale (SUS), and user validation interviews. The prototype achieved full traceability from farmer to consumer, with a mean SUS score of 78,5 (good). Stakeholders reported improved transparency and trust, noting a 40% reduction in verification time compared to manual certification. The system also demonstrated potential for direct incentive mechanisms to support sustainability practices via smart contracts. This research contributes an applicable model for digital transformation in agro-supply chains and offers a replicable framework for integrating emerging technologies into rural MSMEs. Future work should extend multi-site trials, mobile integration, and evaluation of economic impact and carbon footprint tracking.